Pengelolaan Evaluasi Aspek Sosial dalam Pembelajaran Matematika Kurikulum 2013 di Sekolah Menengah Pertama - Emi Fitriyani; Sutama Sutama; Sabar Narimo (Universitas Muhammadiyah Surakarta, 2016)
The purpose of this research is: to described the management of learning mathemathics evaluation on social aspecs which is commited by teacher to the student of Junior High School in Sirampog, District Brebes. This research is research development (Research and Development) which originates from certain problems and continued with Quasi Experimental, that is about the management of of learning mathemathics curriculum 2013 evaluation, and measurement of effectiveness by comparing the result of assesment before developed with already developed by using kualitatif deskription. According to the result of research and discussion that has been done, then researcher can conclude as following statement: Management of learning mathemathics evaluation with curriculum 2013 in Junior High School in Sirampog District Brebes, has been make an assesment optimally, but in the attitude competence especially in self and inter student assesment were not maximized because many teacher give a general declaration not focus on mathemathics, and also this evaluation is only implemented in early curriculum 2013. In the recent time, many teacher are not evaluate and assesment instrument is not change. However, evaluation must be develop and consistent, in order to become better.